Emergence and Spread of Different ESBL-Producing Salmonella enterica Serovars in Hospitalized Horses Sharing a Highly Transferable IncM2 CTX-M-3-Encoding Plasmid - Dor, Ziv; Shnaiderman-Torban, Anat; Kondratyeva, Kira; Davidovich-Cohen, Maya; Rokney, Assaf; Steinman, Amir; Navon-Venezia, Shiri (Frontiers in Microbiology, 2020)
Salmonella enterica is a major causative pathogen of human and animal gastroenteritis. Antibiotic resistant strains have emerged due to the production of extended-spectrum β-lactamases (ESBLs) posing a major health concern. With the increasing reports on ESBL-producing Enterobacterales that colonize companion animals, we aimed to investigate ESBL dissemination among ESBL-producing Salmonella enterica (ESBL-S) in hospitalized horses. We prospectively collected ESBL-S isolates from hospitalized horses in a Veterinary-Teaching Hospital during Dec2015-Dec2017. Selection criteria for ESBL-S were white colonies on CHROMagarESBL plates and an ESBL phenotypic confirmation. Salmonella enterica serovars were determined using the Kaufmann-White-Le-Minor serological scheme. ESBL-encoding plasmids were purified, transformed and compared using restriction-fragment-length polymorphism (RFLP). Whole genome sequencing (Illumina and MinION platforms) were performed for detailed phylogenetic and plasmid analyses. Twelve ESBL-S were included in this study. Molecular investigation and Sequence Read Archive (SRA) meta-analysis revealed the presence of three unique Salmonella enterica serovars, Cerro, Havana and Liverpool, all reported for the first time in horses. PFGE revealed the clonal spread of S. Cerro between seven horses. All twelve isolates carried blaCTX-M-3 and showed an identical multidrug resistance profile with co-resistance to trimethoprim/sulfamethoxazole and to aminoglycosides. Plasmid RFLP proved the inter-serovar horizontal spread of a single blaCTX-M-3-encoding plasmid. Complete sequence of a representative plasmid (S. Havana strain 373.3.1), designated pSEIL-3 was a-86.4 Kb IncM2 plasmid, that encoded nine antibiotic resistance genes. pSEIL-3 was virtually identical to pCTX-M3 from Citrobacter freundii, and showed high identity (>95%) to six other blaCTX-M-3 or blaNDM-1 IncM2 broad host range plasmids from various Enterobacterales of human origin. Using a specific six gene-based multiplex-PCR, we detected pSEIL-3 in various Enterobacterales species that co-colonized the horses’ gut. Together, our findings show the alarming emergence of ESBL-S in hospitalized horses associated with gut shedding and foal morbidity and mortality. We demonstrated the dissemination of CTX-M-3 ESBL among different serovars due to the transmission of a broad-host-range plasmid. This report highlights horses as a zoonotic reservoir for ESBL-S, including highly transmissible plasmids that may represent a ‘One-Health’ hazard. This risk calls for the implementation of infection control measures to monitor and control the spread of ESBL-S in hospitalized horses.